Statins and the risk of polyneuropathy: A systematic review and two meta-analyses - Wannarong T. (2023)
Introduction/Aims: Previous studies have shown inconsistent data on the relationship between statin use and polyneuropathy (PN). The current systematic review and meta-analyses were conducted to comprehensively investigate the risk of incident PN among statin-users compared with non-users by identifying all available studies and summarizing their results. Methods: A systematic review was conducted from MEDLINE and EMBASE databases from inception to October 31, 2020. We included cohort and case–control studies that compared the risk of incident PN between statin-users and non-users. Point estimates and standard errors from eligible studies were pooled together using the generic inverse variance method. Results: Of 4968 retrieved articles, 6 studies in non-diabetic populations and 2 studies in diabetic populations fulfilled the inclusion criteria. Two meta-analyses were performed. The pooled analyses did not find a statistically significant association between the use of statins and risk of incident PN with the pooled odds ratio of 1.24 (95% confidence interval [CI], 0.88–1.76; I2 74%) and 0.82 (95% CI, 0.56–1.21; I2 80%) in non-diabetic and diabetic groups respectively. Discussion: No significant association between the use of statins and the risk of PN was observed in this systematic review and these two meta-analyses. However, there was a high degree of heterogeneity of the meta-analyses.